Debt Relief for the Financially Vulnerable: Impact on Employment, Welfare Receipt, and Mental Health - Ernst-Jan de Bruijn; Heike Vethaak; Pierre Koning; Marike Knoef (Institute of Labor Economics (IZA), 2023)
We study the labor market and mental health impacts of debt relief among financially vulnerable individuals. We exploit a cutoff rule used by a Dutch welfare office to determine eligibility to debt relief of welfare debts. We use this cutoff as an instrument in both a fuzzy regression discontinuity and instrumented difference-in-difference design. With administrative data, we estimate economically small and insignificant effects of debt relief on employment, earnings, welfare receipt, and medication use for mental health problems. Subgroup analyses suggest that debt relief increases employment among debtors with larger welfare debts. The larger amount of debt relief for this group has probably a stronger potential to improve their overall debt position.
Keywords: G51; I38; J22; J64; J68; 330; debt relief; welfare debts; welfare recipients; fuzzy regression discontinuity design; instrumented difference-in-difference